KANDUNGAN NITROGEN, PHOSPOR, KALIUM DAN SULFUR PADA PUPUK ORGANIK CAIR (Poe) KOTORAN SAP! SETELAH MELALUI PROSES DIGESTER Dl DESA TAMANAN KECAMATAN SUKOMORO KABUPATEN MAGETAN - Renik Wijianti; Beny Suyanto; Sujangi . (Poltekkes Kemenkes Surabaya, 2014)
Treatment of cattle wastes is one effort that is quite beneficial and can reduce the negative impacts on theenvironment One way of utilizing livestock manures or organic materials is through the use of biogas.This is rather appropriate since majority of the population reside in rural areas. Meanwhile, the wastegenerated out of the biogas digester can be used as liquid organic fertilizer (LOF) with high nutrientcontents suitable for plants .This experimental study was aimed to determine the content of nitrogen ( N ) , phosphorus ( P ) ,potassium ( K ) , and sulphur ( S ) as a liquid Organic fertilizer ( LOF). This investigation was run usingone group pretest posttest design. Raw cow dung was processed in biogas digesters ( max 3 m3 ) withdetention time ( ) of 7 days, 14 days and 21 days, and the content of N r P , K ,Swill be measuredbefore and after the process in the digester.In the examination before the process,the N content ( 0.10 % ), Pcontent ( 1.13 % ), content of K ( 0.59% ) content of 5 ( 1.19 % ). After the 7 , 14 and 21 days the N content increased from its original state.The highest increment was at day 21, with a large increase of ( 41.2 % ). The element P ( td ) 7 , 14 and21 days have shown a continuous decline and the highest was on day 21 that reached ( 30.08 % ). Forelements of K and S for ( td ) 7, 14 and 21 days have contmuously increased. The highest generation rateof the element K on day 21 reached ( 15.7 % ) and 5 reached ( 43.6 % ). It appeared that the longer theprocess in the digester, the N, K and S contents is increasing although it remained below the standarddeSignated in Permentan 28/ Permentan I 0T.140 I 2/2009. While the P element on the contrary wasdecreasing and there were indications of the longer the process in the digester the greater the decline.This indicated that the Pelement much needed by the bacteria in the fermentation process.An increase in the content of N, K and S as a nutrient for plant growth as generated